Evaluation of localized flux and loss distribution in the corner joint and T joint of 1000 kVA transformer core - Shahanom Uthman (School of Electrical System Engineering, 2013)
The objective of this research work is to assess the performance of three type of transformer core namely the 45° V notch T joint with two different overlap distance and lastly with butt lap core design.